ANALISIS PENENTUAN HARGA POKOK PRODUKSI DALAM MENENTUKAN HARGA JUAL PRODUK (STUDI EMPIRIS PADA UMKM DENDENG SAPI DI BANDA ACEH) - Ruthia Bahri; Rahmawaty Rahmawaty (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this study was to analyze the determination of cost of goods manufactured by using full costing and variable costing, approachment and to get the information about the difference of selling price between the one which is stated by MSMEs in beef jerky processing industry in Banda Aceh and the one which is the result based on cost plus pricing method. This type of research is descriptive analysis. Based on certain criterias, there are 3 MSMEs as the samples of the research. This research shows that the cost of production of the full costing method is greater than the variable costing method. Results of determining the selling price of products also shows that there is a difference between the selling price of the products specified MSMEs of beef jerky with a selling price obtained from cost plus pricing method.